Mood, Being-with-others and Disruptive Behavior in the Classroom: A Psychological Perspective Encounters Phenomenology - Magnar Ødegård (University of Bologna, 2020)
This article is part of the project "Teachers' Skillful Coping with Disruptive Behavior in Norwegian and American Classrooms". Questions raised are how disruptive behavior could affect teachers' being-with-students and how moods could influence how they cope with such behavior. I argue that classroom practices are characterized by "shared attunement" and that there is an interdependence between teachers and students. Another argument is that disruptive behavior could influence teachers' moods negatively. I also explore how teachers could navigate these moods when they encounter student-behavior they perceive as challenging. The analysis in the article has its roots within the field of psychology. It is interested in crossing this with phenomenology in the context of how teachers cope with disruptive behavior in classrooms.